2018
DOI: 10.1029/2018wr023199
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Attenuation and Lag Time in Fractured Rock: Theory and Field Measurements From Joint Heat and Solute Tracer Tests

Abstract: The modeling and prediction of heat transfer in fractured media is particularly challenging as hydraulic and transport properties depend on a multiscale structure that is difficult to resolve. In addition to advection and dispersion, heat transfer is also impacted by thermal attenuation and lag time, which results from fracture-matrix thermal exchanges. Here we derive analytical expressions for thermal lag time and attenuation coefficient in fractured media, which quantify the effect of fracture geometry on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 70 publications
0
44
0
Order By: Relevance
“…The storage and transport of fluids in fault zones is generally assumed to be highly partitioned owing to the structural complexity of fault‐related fracture systems (Bonnet et al, ; Kim et al, ; Sibson, ; Tchalenko, ) and sharp contrasts in hydraulic properties (Bense et al, ; Brace, , ; Caine et al, ; Evans & Goddard, ; Roques et al, ). This affects processes in the Earth's crust operating on a broad range of scales, from the emergence of flow pathways (Tsang & Neretnieks, , and references therein) channeling solute (Kang et al, ) and heat transport (De La Bernardie et al, ; Fox et al, ; Geiger & Emmanuel, ; Klepikova et al, ) to convecting instabilities (Murphy, ; Patterson et al, ), frictional heating (Mase & Smith, ; Rice, ; Vredevoogd et al, ), dynamic fault weakening (Byerlee, ), and earthquake sequences (Jansen et al, ; Miller et al, ; Noir et al, ; Nur & Booker, ; Ross et al, ; Shapiro et al, ; Wang et al, ). Tracking how fluids migrate in faults in situ can therefore provide insights on key geological and physical processes.…”
Section: Introductionmentioning
confidence: 99%
“…The storage and transport of fluids in fault zones is generally assumed to be highly partitioned owing to the structural complexity of fault‐related fracture systems (Bonnet et al, ; Kim et al, ; Sibson, ; Tchalenko, ) and sharp contrasts in hydraulic properties (Bense et al, ; Brace, , ; Caine et al, ; Evans & Goddard, ; Roques et al, ). This affects processes in the Earth's crust operating on a broad range of scales, from the emergence of flow pathways (Tsang & Neretnieks, , and references therein) channeling solute (Kang et al, ) and heat transport (De La Bernardie et al, ; Fox et al, ; Geiger & Emmanuel, ; Klepikova et al, ) to convecting instabilities (Murphy, ; Patterson et al, ), frictional heating (Mase & Smith, ; Rice, ; Vredevoogd et al, ), dynamic fault weakening (Byerlee, ), and earthquake sequences (Jansen et al, ; Miller et al, ; Noir et al, ; Nur & Booker, ; Ross et al, ; Shapiro et al, ; Wang et al, ). Tracking how fluids migrate in faults in situ can therefore provide insights on key geological and physical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Heat has been widely used as active and passive tracers for the characterization of thermal transport and hydrological processes in aquifers [1][2][3][4][5][6][7]. For instance, it has been shown in many examples during the last 20 years that the use of heat is very efficient for characterizing surface-groundwater exchanges [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies have shown that borehole temperature profiles under induced fluid flow conditions by pumping in an adjacent borehole could be used to estimate fracture interconnections [20] and hydraulic properties [21]. Very recently, thermal tracer tests have also shown their efficiency to demonstrate the impact of flow channeling on heat transport [5,22,23]. In particular, it has been shown that flow channeling may highly reduce thermal transit times and improve thermal recovery during thermal tracer tests [5,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations